Free-standing and highly conductive PEDOT nanowire films for high-performance all-solid-state supercapacitors. Issue 3 (2nd January 2019) - Ni, Dan; Chen, Yuanxun; Song, Haijun; Liu, Congcong; Yang, Xiaowei; Cai, Kefeng
Abstract : Flexible solid-state supercapacitors based on free-standing PEDOT NW films with PVA–H2 SO4 –polydopamine robust gel films show high electrochemical performance. Abstract : Recently, flexible and portable supercapacitors (SCs) have attracted increasing interest. PEDOT is a promising electrode material due to its high electrical conductivity, excellent environmental stability and cycling stability; however, the electrochemical performance of free-standing PEDOT films has not been reported yet. Herein, a simple and low-cost modified self-assembled micellar soft-template method followed by vacuum-assisted filtration has been developed to synthesize flexible and free-standing PEDOT nanowire (NW) films with very high electrical conductivity (∼1340 S cm −1 ). The PEDOT NW film electrode with excellent flexibility exhibits excellent electrochemical performance (specific capacitance of 667.5 mF cm −2 at 1 mA cm −2 and good cycling stability). A flexible solid-state PEDOT NW film-based SC shows high specific capacitances of 413.5 mF cm −2 at 1 mA cm −2 and 306.0 mF cm −2 at 50 mA cm −2, an outstanding energy density of 48.3 μWh cm −2 at a power density of 0.22 mW cm −2 and a superior power density of 16.77 mW cm −2 at an energy density of 19.1 μWh cm −2 . The desirable combination of excellent flexibility, high electrical conductivity, excellent electrochemical properties, and facile process scalability makes the PEDOT NW film particularly promising for portable and flexible electronics.